On the parameters of the Lewis metric for the Lewis class - Silva, M. F. A. da [UNESP]; Herrera, L.; Paiva, F. M.; Santos, N. O. (IOP Publishing, 1995)
The physical and geometrical meaning of the four parameters of the Lewis metric for the Lewis class are investigated. Matching this spacetime to a completely anisotropic, rigidly rotating, fluid cylinder, we find from the junction conditions that the four parameters are related to the vorticity of the source. Furthermore, it is shown that one of the parameters must vanish if one wishes to reduce the Lewis class to a locally static spacetime. Using the Cartan scalars it is shown that the Lewis class does not include Minkowski as a special class globally, and that it is not locally equivalent to the Levi-Civita metric. It is also shown that, in contrast with the Weyl class, the parameter responsible for the vorticity appears explicitly in the expression for the Cartan scalars. Finally, to enhance our understanding of the Lewis class, we analyse the van Stockum metric.